Detailed flow patterns in the nasal cavity - Kelly, J. T; Prasad, A. K; Wexler, A. S (Journal of applied physiology (1985), 2000)
Department of Mechanical Engineering, University of Delaware, Newark, Delaware 19716-3140 The human nasal cavity filters and conditions inspired air while providing olfactory function. Detailed experimental study of nasal airflow patterns has been limited because of the complex geometry of the nasal cavity. In this work, particle image velocimetry was used to determine two-dimensional instantaneous velocity vector fields in parallel planes throughout a model of the nasal cavity that was subjected to a nonoscillatory flow rate of 125 ml/s. The model, which was fabricated from 26 computed tomography scans by using rapid prototyping techniques, is a scaled replica of a human right nasal cavity. The resulting vector plots show that the flow is laminar and regions of highest velocity are in the nasal valve and in the inferior airway. The relatively low flow in the olfactory region appears to protect the olfactory bulb from particulate pollutants. Low flows were also observed in the nasal meatuses, whose primary function has been the subject of debate. Comparison of sequentially recorded data suggests a steady flow. particle image velocimetry; nasal airflow; human; replica model